Simulated radiance patterns for Mie absorbing finite clouds - Klehr, John T., author; McKee, Thomas B., author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 1978)
Calculations were made of the scattering of sunlight from finite and infinite clouds composed of particles which were capable of both scattering and absorption. Results of Mie absorption upon shortwave irradiance values and radiance patterns of finite (cubic) and infinite (layer) clouds are presented over a range of single scattering albedos (ωₒ) from 1.0 to 0.9 and solar zenith angles of 0°, 30°, and 60°. A finite cloud is shown to absorb a smaller fraction of incident light than an infinite cloud at all sun angles and values of single scattering albedo. Both cloud types show a maximum fraction of absorption with the sun vertical. In an infinite cloud as the solar zenith angle is increased the absorption decreases in the lower layers of the cloud, while in the finite cloud the lower layers increase in absorption as the solar zenith angle is increase. Radiance patterns are shown to be primarily determined by cloud and solar geometries with absorption tending to reduce the radiance values and only slightly flatten the radiance patterns. If the optical depth is increased from 20 to 60 with the sun vertical the finite cloud shows a larger increase in fractional absorption than the infinite, but even at large optical depths (60) and large absorption values (ωₒ = 0.9) the finite cloud still allows a significant fraction of light to escape downward from its sides.
March 1978.
Keywords: Mie scattering; Cloud physics